RETRACTED: Resource of copying strategies in the prevention of professional burnout of engineering specialists - Shcherbakova Tatyana; Stashkova Tatyana; Marinenko Tatyana; Akopyan Marina; Gshiyants Roman; Sargsyan Levon (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001